Gaza : a history - Filiu, Jean-Pierre.; King, John. (New York, New York : Oxford University Press, 2014)
"Through its millennium-long existence, Gaza has often been bitterly disputed while simultaneously and paradoxically enduring prolonged neglect. Squeezed between the Negev and Sinai desert on the one hand and the Mediterranean Sea on the other, Gaza was contested by the Pharaohs, the Persians, the Greeks, the Romans, the Byzantines, the Arabs, the Fatimids, the Mamluks, the Crusaders, and the Ottomans. Napoleon had to secure it in 1799 to launch his failed campaign on Palestine. In 1917, the British Empire fought for months to conquer Gaza, before establishing its mandate on Palestine. In 1948, 20,000 Palestinians sought refuge in Gaza, a marginal area that neither Israel nor Egypt wanted. Palestinian nationalism grew there, and Gaza has since found itself at the heart of Palestinian history."--
Gaza before the Strip : The crossroads of empires -- The Islamic era -- The British mandate -- 1947-67: The generation of mourning : The catastrophe -- Refugees and fedayin -- The first occupation -- Nasser's children -- 1967-87: The generation of dispossession : The four years war -- The era of the notables -- The alien peace -- The new wave -- 1987-2007: The generation of the intifadas : The revolt of the stones -- A sharply limited authority -- Days of fury -- One Palestine against another -- Conclusion : The generation of impasses? : Five years in the ruins.
Includes bibliographical references (pages 375-379) and indexes.
Translation of: Histoire de Gaza.
Keywords: Gaza -- History; Gaza Strip -- History; Gaza Strip -- Economic conditions; Gaza Strip -- Social conditions; Gaza Strip -- Politics and government; Arab-Israeli conflict; Social conflict -- Gaza Strip -- History; Land settlement -- Gaza Strip -- Gaza